Factors Influencing Accounting Students’ Intentions to Use Generative AI (ChatGPT) - Nastasya Cindy Hidajat; Fransiska Natalia Kosasih; Sri Sundari; Kartini Kartini (Advances: Jurnal Ekonomi & Bisnis, 2026)
Purpose: This study aims to analyze the factors influencing accounting students' intention to use AI, specifically ChatGPT. This study employs a quantitative approach, adopting the Technology Acceptance Model (TAM) with perceived usefulness and perceived ease of use, and expands it to include the variables of trust and social influence. The research hypothesis states that these four variables have a positive and significant effect on the intention to use GenAI. Research Method: Data were collected via a questionnaire administered to accounting students who had used or were familiar with ChatGPT. The sample was selected through purposive sampling among students at Tarumanagara University in West Jakarta, yielding 125 respondents. Data analysis was conducted using Structural Equation Modeling-Partial Least Squares (SEM-PLS). Results and Discussion: The study indicates that perceived usefulness, perceived ease of use, trust, and social influence have a positive and significant effect on behavioral intention. These findings underscore the importance of improving digital literacy, providing guidelines for ethical use, and securing support from instructors and institutions in integrating ChatGPT into accounting education. Implications: This study makes a theoretical contribution to the development of AI-based technology adoption models and a practical contribution to educational institutions by informing the design of GenAI integration strategies to optimize accounting education. Originality: A study of the factors influencing the intention to use ChatGPT GenAI among accounting students in Indonesia, specifically at Tarumanagara University, as research on GenAI in accounting education remains limited.